2010
DOI: 10.3846/jbem.2010.26
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise Resource Planning Systems Implementation as a Complex Project: A Conceptual Framework

Abstract: Abstract. The purpose of this paper is to investigate current literature on critical success factors (CSF) and risk factors (RF) of enterprise resource planning (ERP) system implementation and provide a systemic explanation of complexities involved in such implementation. This study will compile literature that highlighted possible references to CSFs of ERP implementations, definition of complex projects and ERP are compared with project management and project governance impacts. By analyzing highly likely CFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 42 publications
0
23
0
1
Order By: Relevance
“…These benefits are most likely to be spanned over the whole supply chain due to better forecasting, lower rework and product returns, and increased customer satisfaction. Ghosh and Skibniewski (2010) pointed out that the enterprise resource planning (ERP) systems commonly require changes in business processes to best practices determined by the ERP vendor's supported system which may not match with the ERP adopter's business processes. Therefore, firms must be willing to continue to learn and adapt in order to succeed within the context of environmental complexities.…”
Section: Discussionmentioning
confidence: 99%
“…These benefits are most likely to be spanned over the whole supply chain due to better forecasting, lower rework and product returns, and increased customer satisfaction. Ghosh and Skibniewski (2010) pointed out that the enterprise resource planning (ERP) systems commonly require changes in business processes to best practices determined by the ERP vendor's supported system which may not match with the ERP adopter's business processes. Therefore, firms must be willing to continue to learn and adapt in order to succeed within the context of environmental complexities.…”
Section: Discussionmentioning
confidence: 99%
“…• Fit CSFs to phase of implementation Basoglu, Daim and Kerimoglu, 2007;Bradley, 2008;Dery et al, 2006;Dezdar and Sulaiman, 2009;Ehie and Madsen, 2005;Finney and Corbett, 2007;Francoise, Bourgault and Pellerin, 2009;Ghosh and Skibniewski, 2010;Grabski, Leech and Schmidt, 2011;Hong and Kim, 2002;King and Burgess, 2006;Momoh, Roy and Shehab, 2010;Muscatello and Parente, 2006;Ngai, Law and Wat, 2008;Peng and Nunes, 2009;Petroni, 2002;Powell and Strandhagen, 2011;Robey, Ross and Boudreau, 2002;Shaul and Tauber, 2013;Yen, Idrus and Yusof, 2011;Skok and Legge, 2002;…”
Section: Referencesmentioning
confidence: 99%
“…Ghosh and Skibniewski (2010) indicated that "Enterprise Resource Planning (ERP) systems are among the most important business information technologies that emerged during the last decade." ERP emerged in the late 1980s and early 1990s out of the necessity for creating new systems that integrate all the functions of an organization together in order to be able to deal with the highly competitive business environment and the increasingly rapid advancements in IT systems.…”
Section: Previous Workmentioning
confidence: 99%